2023
DOI: 10.1007/s41669-023-00418-x
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Strategies for Caring for Critically Ill Patients with COVID-19 in Tanzania

Abstract: Background The resources for critical care are limited in many settings, exacerbating the significant morbidity and mortality associated with critical illness. Budget constraints can lead to choices between investing in advanced critical care (e.g. mechanical ventilators in intensive care units) or more basic critical care such as Essential Emergency and Critical Care (EECC; e.g. vital signs monitoring, oxygen therapy, and intravenous fluids). Methods We investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 63 publications
0
12
0
1
Order By: Relevance
“…A total of 31 studies proceeded to quality assessment, of which 13 were excluded due to the presence of very serious limitations ( Table 4 ). Finally, 18 studies of acceptable quality were included in this two-year update ( Carta and Conversano, 2021 ; Congly et al, 2021 ; Ruggeri et al, 2022a ; Ruggeri et al, 2022b ; Dijk et al, 2022 ; Goswami et al, 2022 ; Kelton et al, 2022 ; Lau et al, 2022 ; Metry et al, 2022 ; Park et al, 2022 ; Rafia et al, 2022 ; Savinkina et al, 2022 ; Yeung et al, 2022 ; Alamer et al, 2023 ; Arwah et al, 2023 ; Kowal et al, 2023 ; Ruggeri et al, 2023 ; Shah et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 31 studies proceeded to quality assessment, of which 13 were excluded due to the presence of very serious limitations ( Table 4 ). Finally, 18 studies of acceptable quality were included in this two-year update ( Carta and Conversano, 2021 ; Congly et al, 2021 ; Ruggeri et al, 2022a ; Ruggeri et al, 2022b ; Dijk et al, 2022 ; Goswami et al, 2022 ; Kelton et al, 2022 ; Lau et al, 2022 ; Metry et al, 2022 ; Park et al, 2022 ; Rafia et al, 2022 ; Savinkina et al, 2022 ; Yeung et al, 2022 ; Alamer et al, 2023 ; Arwah et al, 2023 ; Kowal et al, 2023 ; Ruggeri et al, 2023 ; Shah et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Included studies evaluated interventions in community or outpatient settings (5/18) ( Goswami et al, 2022 ; Park et al, 2022 ; Savinkina et al, 2022 ; Yeung et al, 2022 ; Ruggeri et al, 2023 ), where patients are at risk of admission to hospital, or an inpatient hospital setting (11/18) ( Carta and Conversano, 2021 ; Congly et al, 2021 ; Ruggeri et al, 2022a ; Ruggeri et al, 2022b ; Dijk et al, 2022 ; Kelton et al, 2022 ; Lau et al, 2022 ; Rafia et al, 2022 ; Alamer et al, 2023 ; Kowal et al, 2023 ; Shah et al, 2023 ); one study included both settings (1/18) ( Metry et al, 2022 ). One study evaluated point-of-care tests in an unspecified health facility (1/18) ( Arwah et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For critically unwell patients, open and functional interdepartmental linkages and communication systems are vital owing to the time-critical nature of their conditions, and the fact that they often cannot advocate for themselves. If the turn-around-time is to be reduced, it is, therefore, essential to eliminate these administrative stumbling blocks, to reduce the congestion in the emergency care pathways, and capitalise on the cost-effectiveness of the basic emergency care interventions 44–47…”
Section: Discussionmentioning
confidence: 99%
“…26 In Tanzania, preliminary analysis has found that the probability of EECC provision being cost-effective is greater than 95% while more advanced critical care is not cost-effective based on commonly used thresholds. [26][27][28][29] While these estimates provide a good benchmark, they have limitations; observational studies on the clinical effectiveness of EECC are not yet available. However, a focus on delivering quality EECC at scale would also promote equity, making it a priority for inclusion in universal health coverage strategies.…”
Section: Summary Boxunclassified